2013
DOI: 10.1364/oe.21.011965
|View full text |Cite
|
Sign up to set email alerts
|

The study of optical band edge property of bismuth oxide nanowires α-Bi_2O_3

Abstract: The α-phase Bi(2)O(3) (α-Bi(2)O(3)) is a crucial and potential visiblelight photocatalyst material needless of intentional doping on accommodating band gap. The understanding on fundamental optical property of α-Bi(2)O(3) is important for its extended applications. In this study, bismuth oxide nanowires with diameters from tens to hundreds nm have been grown by vapor transport method driven with vapor-liquid-solid mechanism on Si substrate. High-resolution transmission electron microscopy and Raman measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 18 publications
11
49
0
Order By: Relevance
“…6. The Raman peaks observed were in good agreement with the literature values [35]. The major Raman bands at 528.5, 448.5, 314.4, 211.3 and 152.4 cm −1 are attributed to skeletal Bi-O vibrations in as prepared Bi 2 O 3 .…”
Section: Resultssupporting
confidence: 89%
“…6. The Raman peaks observed were in good agreement with the literature values [35]. The major Raman bands at 528.5, 448.5, 314.4, 211.3 and 152.4 cm −1 are attributed to skeletal Bi-O vibrations in as prepared Bi 2 O 3 .…”
Section: Resultssupporting
confidence: 89%
“…2A seem that they are corresponding to A g mode. The results of the observed Raman shift frequencies and also the previous data reported by Denisov et al [43] and Ho et al [17] to the A g mode are represented in Table 2. Raman spectral studies confirmed that the prepared BiO-1 and BiO-2 samples are precisely single phase aBi 2 O 3 ; however, BiO-3 sample is b-phase of Bi 2 O 3 .…”
Section: Resultssupporting
confidence: 56%
“…Stable phases are a-and d-Bi 2 O 3 , while the others are high-temperature metastable phases [29]. a-Bi 2 O 3 is thermodynamically the most stable phase in the range of 25 8C to 730 8C [17,30]. At 730 8C, aBi 2 O 3 transforms into d-phase and remains stable until reach its melting point at 825 8C [31].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations